Surveying - McCormac, Jack C.; Davis, William J., 1959-; Sarasua, Wayne, 1961- (John Wiley & Sons, Inc, 2014)
"McCormac's 6th edition of Surveying provides a basic overview to help readers understand and communicate with surveyors. New features include more applications in engineering areas such as environmental, transportation, geotechnical, construction; more applications to GIS and GPS; added coverage of Geomatics, including setting up data to do analysis and make decisions; and more examples and increase number of homework problems"--
Includes index.
Keywords: Surveying